Methodological uncertainties in drug-receptor binding free energy predictions based on classical molecular dynamics. (April 2021) - Procacci, Piero
Graphical abstract: Highlights: Computational approaches are becoming an essential tool in modern drug design. Development of automated workflows from docking to MD techniques for drug design. Reliable absolute binding free energies are a key requirement in virtual screening. Free energy perturbation methods are plagued by uncertainties due to sampling. Nonequilibrium approaches can be effectively used for absolute binding free energies. Abstract : Computational approaches are becoming an essential tool in modern drug design and discovery, with fast compound triaging using a combination of machine learning and docking techniques followed by molecular dynamics binding free energies assessment using alchemical techniques. The traditional MD-based alchemical free energy perturbation (FEP) method faces severe sampling issues that may limits its reliability in automated workflows. Here we review the major sources of uncertainty in FEP protocols for drug discovery, showing how the sampling problem can be effectively tackled by switching to nonequilibrium alchemical techniques.